2010
DOI: 10.2495/sc100441
|View full text |Cite
|
Sign up to set email alerts
|

Working scheme for safe management of construction and demolition wastes containing hazardous substances

Abstract: Wastes from construction and demolition (C&D) are mainly composed of inert materials. A small proportion of C&D wastes contain substances which make them hazardous, for example, those wastes containing asbestos, mineral fibres, additives, some paints and resins, among others.On the other hand, in the manufacturing of several products used in the construction industry many hazardous substances are utilized. In most cases these materials are relatively safe while being used, but they become dangerous when they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The Australian, Italian, and US regulations (Australian Minister for Employment, 2016b; Italian Ministry of Health and Ministry of Industry Trade and Crafts, 1994; Occupational Safety and Health Administration, 2009) state that ACBM waste should be evacuated from the job site according to the nature of the work and the volume of waste generated, as soon as possible (i.e., either at the end of each day or week, before the containers and/or waste stockpile area are full, or at the end of the removal work). The storage area should be well ventilated, protected from sun and rain, separated from other waste to avoid mixing, with restricted access, and display warning signs of the presence of ACBM waste (Mateo et al, 2013; McKenna, 2016; Quaranta et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian, Italian, and US regulations (Australian Minister for Employment, 2016b; Italian Ministry of Health and Ministry of Industry Trade and Crafts, 1994; Occupational Safety and Health Administration, 2009) state that ACBM waste should be evacuated from the job site according to the nature of the work and the volume of waste generated, as soon as possible (i.e., either at the end of each day or week, before the containers and/or waste stockpile area are full, or at the end of the removal work). The storage area should be well ventilated, protected from sun and rain, separated from other waste to avoid mixing, with restricted access, and display warning signs of the presence of ACBM waste (Mateo et al, 2013; McKenna, 2016; Quaranta et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, ACBM wastes that are highly deteriorated, broken, or fragmented can release fibers only with hand pressure and represent a higher risk for the population and the environment (Paglietti et al, 2016). Thus, ACBM waste exhibits hazardous characteristics that require special management and strict controls (Szymańska & Lewandowska, 2019), which also precludes ACBM waste recycling and requires an appropriate final disposal (del Río Merino et al, 2010;Li et al, 2014;Quaranta et al, 2010;Raleigh et al, 1995;Silva Santos & Penteado Marchesini, 2018). Related to ACBM waste recycling, during this research, a store that purchases and sells recycled ACBM waste was identified near the city of Bogotá, the capital of Colombia (see Supporting Information: Figure 1S).…”
Section: Stage 2-removal Of Installed Acbmmentioning
confidence: 99%